Disease-specific phenotypes in dopamine neurons from human iPS-based models of genetic and sporadic Parkinson's disease - Sánchez-Danés, Adriana (WILEY-VCH Verlag, 2012)
Induced pluripotent stem cells (iPSC) offer an unprecedented opportunity to model human disease in relevant cell types, but it is unclear whether they could successfully model age-related diseases such as Parkinson's disease (PD). Here, we generated iPSC lines from seven patients with idiopathic PD (ID-PD), four patients with familial PD associated to the G2019S mutation in the Leucine-Rich Repeat Kinase 2 (LRRK2) gene (LRRK2-PD) and four age- and sex-matched healthy individuals (Ctrl). Over long-time culture, dopaminergic neurons (DAn) differentiated from either ID-PD- or LRRK2-PD-iPSC showed morphological alterations, including reduced numbers of neurites and neurite arborization, as well as accumulation of autophagic vacuoles, which were not evident in DAn differentiated from Ctrl-iPSC. Further induction of autophagy and/or inhibition of lysosomal proteolysis greatly exacerbated the DAn morphological alterations, indicating autophagic compromise in DAn from ID-PD- and LRRK2-PD-iPSC, which we demonstrate occurs at the level of autophagosome clearance. Our study provides an iPSC-based in vitro model that captures the patients' genetic complexity and allows investigation of the pathogenesis of both sporadic and familial PD cases in a disease-relevant cell type.